1997
DOI: 10.1136/bmj.315.7117.1202
|View full text |Cite
|
Sign up to set email alerts
|

What investigations and procedures do patients in hospices want? Interview based survey of patients and their nurses

Abstract: Slevin et al reported that patients with cancer were much more likely to opt for chemotherapy with minimal chance of benefit than were their professional carers and people without cancer.1 They also said that attitudes changed dramatically once cancer had been diagnosed. We investigated the attitudes of terminally ill patients in our hospice towards investigations and invasive procedures and compared these with the attitudes of their nurses. Subjects, methods, and resultsRandomly selected inpatients with advan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
2

Year Published

1998
1998
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 4 publications
0
11
0
2
Order By: Relevance
“…Teno, personal communication, August 2015). [41][42][43][44][45] This disparity is likely a result of several factors, but may be explained in part by the use of palliative chemotherapy and blood transfusions late in the disease course, a practice that is shown to be effective 46 and desired, 47 but also cost prohibitive for hospice facilities. 48 Further work is required to identify cost-effective solutions to provide quality end-of-life care to these patients.…”
Section: Discussionmentioning
confidence: 99%
“…Teno, personal communication, August 2015). [41][42][43][44][45] This disparity is likely a result of several factors, but may be explained in part by the use of palliative chemotherapy and blood transfusions late in the disease course, a practice that is shown to be effective 46 and desired, 47 but also cost prohibitive for hospice facilities. 48 Further work is required to identify cost-effective solutions to provide quality end-of-life care to these patients.…”
Section: Discussionmentioning
confidence: 99%
“…While such advances do represent the medicalization of hospice, 13 this need not be seen as a detriment but as an indication that the ideals of hospice are being incorporated into conventional clinical care. The finding in one survey that hospice patients were more likely to accept medical interventions than their nurses 14 should caution us to keep in mind interventions that could help terminally ill patients and to discuss these openly with patients so that they understand potential benefits and harms.…”
Section: Natural and Medicalized Deathmentioning
confidence: 99%
“…It is important for the physician to ask the patient his or her wishes and to listen to nurses and social workers, with whom the patient may have established important relationships. One interviewbased study of 23 patients with advanced cancer in hospice care reported that 52% of patients, but no nurses, were in favor of resuscitation [8]. Although opinions can be divergent, most decisions are made by consensus between physicians and the patient, the family or surrogates; major conflicts occur in only 1% of decisions to withhold life-sustaining treatment in incompetent patients [9].…”
Section: It Should Take the Patient's Emotional And Psychological Welmentioning
confidence: 99%